PENGEMBANGAN UBI JALAR UNGU SEBAGAI BAHAN UTAMA DIVERSIFIKASI PANGAN UNTUK MENGATASI STUNTING DI KECAMATAN GOLEWA BARAT KABUPATEN NGADA - Umbu Awang Hamakonda; Igniosa Taus; Marselina Toyo (Jurnal Agriovet, 2024)
Sweet potato (Ipomoea batatas L.) is one of the alternative non-rice carbohydrates that is very beneficial for health because of its high starch, fruit, vitamins, and minerals. In West Golewa District, Ngada Regency, the research objective is to overcome stunting by developing purple sweet potatoes as the main ingredient for food diversification. This study used a qualitative descriptive approach, with a survey starting by determining the location, variables, and data collection. The results showed that the growth of sweet potato as the main component of food diversification to combat stunting has produced purple sweet potato flour products. The results of purple sweet potato flour are processed into various processed products that are given to stunted children, and these processed products are very much liked by stunted children. The use of purple sweet potato raw materials into purple sweet potato flour products is economically profitable and beneficial for health and is very much liked by the community for processed products.